Production of high quality graphene from solid carbon sources

By applying voltage pulses on a high-purity solid carbon source, the problem of structural defects in graphene production is solved, and the production of high-quality graphene is achieved, which significantly improves its performance.

CN119522190APending Publication Date: 2025-02-25J·G·西格尔
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380036164.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-11
Filing Date
2023-03-10
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is prone to structural defects when producing graphene, which affects its performance.

Method used

Provide a high purity solid carbon source and applied voltage pulses thereon to convert to graphene, reducing the presence of external and intrinsic defects by this method.

Benefits of technology

The graphene produced by this method contains less than 200 ppm of external defects and less than 0.01% of internal defects, significantly improving its mechanical properties, thermal properties and electrical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005100154470000011
    Figure HDA0005100154470000011
  • Figure HDA0005100154470000021
    Figure HDA0005100154470000021
  • Figure HDA0005100154470000031
    Figure HDA0005100154470000031
Patent Text Reader

Abstract

The present invention generally relates to systems and methods for producing high quality graphene from a solid carbon source.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Graphene is one of the most promising materials in nanotechnology. The mechanical, thermal and electrical properties of graphene samples with a highly perfect atomic lattice are excellent, but structural defects that can occur during growth or processing degrade the performance of graphene-based devices. There is a need in the art for improved methods of producing high-quality graphene. Summary of the invention

[0002] The present invention relates to methods for producing and using high-purity graphene.

[0003] In one embodiment, the present invention provides a method for producing graphene, the method comprising: a) providing a high-purity solid carbon source; and b) applying a voltage pulse to the solid carbon source to convert the solid carbon source into graphene.

[0004] In one embodiment, the present invention provides a method for producing graphene, the method comprising: a) providing a high purity solid carbon source, wherein the solid carbon source is greater than 99.99% (w / w) elemental carbon; and b) applying a voltage pulse to the solid carbon source to convert the solid carbon source into graphene, wherein the graphene contains less than 200 ppm of extrinsic defects.

[0005] In some embodiments, the solid carbon source is greater than 99.995% (w / w) elemental carbon. In some embodiments, the solid carbon source is greater than 99.999% (w / w) elemental carbon. In some embodiments, the solid carbon source is greater than 99.9995% (w / w) elemental carbon. In some embodiments, the solid carbon source is greater than 99.9999% (w / w) elemental carbon.

[0006] In some embodiments, the graphene comprises less than 100 ppm of extrinsic defects. In some embodiments, the graphene comprises less than 50 ppm of extrinsic defects. In some embodiments, the graphene comprises less than 25 ppm of extrinsic defects. In some embodiments, the graphene comprises less than 10 ppm of extrinsic defects. In some embodiments, the graphene comprises less than 5 ppm of extrinsic defects. In some embodiments, the graphene comprises less than 1 ppm of extrinsic defects.

[0007] In some embodiments, the extrinsic defects are evaluated by Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), inductively coupled plasma optical emission spectroscopy (ICP-OES), ICP-mass spectrometry (ICP-MS), proton induced x-ray emission, x-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), scanning tunneling microscopy (STM), atomic force microscopy (AFM), energy dispersive x-ray analysis (EDX), oxidative combustion, and / or thermogravimetric analysis.

[0008] In some embodiments, the extrinsic defect is oxygen. In some embodiments, the graphene comprises less than 200 ppm of oxygen.

[0009] In some embodiments, the graphene contains less than 0.01% intrinsic defects. In some embodiments, the intrinsic defects include non-sp 2 In some embodiments, the graphene contains less than 0.01% sp 3 In some embodiments, the sp 2 The percentage is at least 95%.

[0010] In some embodiments, the graphene has an I(D) / I(G) ratio of less than 0.2 as measured by Raman spectroscopy. In some embodiments, the graphene has an I(2D) / I(G) ratio between 0.5 and 2 as measured by Raman spectroscopy.

[0011] In some embodiments, the conductivity of the graphene is at least 10 4 In some embodiments, the specific surface area (SSA) of the graphene is greater than 1000 m 2 In some embodiments, the graphene is a graphene flake, and wherein the graphene flake has an average lateral size (D50) of at least 10 μm.

[0012] In some embodiments, the subsequent step b) does not purify the graphene. In some embodiments, the subsequent step b) does not remove extrinsic defects. In some embodiments, the method further comprises step c): mixing the graphene with a binder or dispersant without further purification.

[0013] In some embodiments, the solid carbon source comprises greater than 90% (w / w) amorphous carbon. In some embodiments, the solid carbon source comprises greater than 90% (w / w) graphitic carbon.

[0014] In some embodiments, the solid carbon source is produced by reducing carbon dioxide or carbon monoxide using hydrogen. In some embodiments, the solid carbon source is produced from carbon dioxide and hydrogen via the Bosch reaction. In some embodiments, the amount of hydrogen provided is greater than the stoichiometric ratio required for reducing carbon dioxide or carbon monoxide. In some embodiments, the solid carbon source is produced from carbon monoxide via the Bodo reaction. In some embodiments, the reaction includes a catalyst or a catalyst precursor. In some embodiments, the reaction occurs at room temperature. In some embodiments, the reaction occurs at a temperature of 450°C to 2000°C. In some embodiments, step b) is carried out at atmospheric pressure.

[0015] In some embodiments, the method produces at least one gram of graphene. In some embodiments, the yield of graphene produced from the solid carbon source is at least 90%.

[0016] The present invention is also characterized by an apparatus comprising a combination of: (a) a first component for providing a high-purity solid carbon source by reducing carbon dioxide or carbon monoxide using hydrogen; and (b) a second component for applying a voltage pulse to the solid carbon to convert the solid carbon into graphene.

[0017] definition

[0018] In order to facilitate understanding of the present invention, many terms are defined below and throughout this disclosure. Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs. The terms herein are used to describe specific embodiments of the present invention, but their use does not limit the present invention, except as outlined in the claims.

[0019] Terms such as "a," "an," and "the" are not intended to refer to a singular entity, but include the general class and may be illustrated using a specific example of the general class.

[0020] As used herein, the term "about" refers to a value that is within 10% above or below the stated value.

[0021] As used herein, the term "amorphous" refers to a material, such as an amorphous carbon material, whose constituent atoms, molecules or ions are randomly arranged without a regularly repeating pattern. Amorphous materials may have some local crystallinity (i.e., regularity), but lack long-range order of atomic positions. Pyrolytic carbon materials and / or activated carbon materials are typically amorphous.

[0022] As used herein, the term "defect" refers to a physical anomaly of a material compared to that ideal material, for example a defect is a physical difference between prepared graphene and ideal graphene.

[0023] As used herein, the term "intrinsic defect" refers to a material flaw due to carbon bonding. For example, intrinsic defects are described in Tian et al. Micromachines Vol. 8, 5 163 (2017), which is incorporated herein by reference.

[0024] As used herein, the term "extrinsic defect" refers to a material imperfection due to the presence of foreign atoms (such as non-carbon atoms in graphene). For example, extrinsic defects are described in Tian et al., Micromachines, Vol. 8, 5 163 (2017).

[0025] As used herein, the term “sp 2 Hybridization means that the carbon atom is directly bonded to three other carbon atoms and has a planar geometry. For example, the sp 2 Hybridization.

[0026] As used herein, the term “sp 3 Hybridization means that the carbon atom is bonded to four other atoms and has a tetrahedral geometry. For example, the sp 3 Hybridization. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The following detailed description of embodiments of the present invention will be better understood when read in conjunction with the accompanying drawings. For the purpose of illustrating the present invention, embodiments are shown in the drawings and are now exemplified. However, it should be understood that the present invention is not limited to the precise arrangements and apparatus of the embodiments shown in the drawings.

[0028] Figure 1A , Figure 1B and Figure 1C An embodiment of a chamber for producing solid carbon and / or graphene is shown.

[0029] Figure 2A and Figure 2B An embodiment of the catalyst is shown.

[0030] Figure 3 An embodiment of a gasket is shown. DETAILED DESCRIPTION

[0031] The following description sets forth various examples and specific details to provide a thorough understanding of the claimed subject matter. However, it will be appreciated by those skilled in the art that the claimed subject matter can be practiced without one or more of the specific details disclosed herein. In addition, in some cases, well-known methods, processes, systems, and / or components are not described in detail to avoid unnecessarily obscuring the claimed subject matter. The illustrative embodiments described in the detailed description and the claims are not intended to be limiting. Other embodiments may be utilized, and other changes may be made without departing from the spirit or scope of the subject matter presented herein. It will be readily understood that, as generally described herein, various different configurations may be arranged, substituted, combined, and designed in various aspects of the present disclosure, all of which are expressly contemplated and become a part of the present disclosure.

[0032] Without limiting the scope of the invention, the present invention relates to the production of high-purity graphene. Specifically, the present disclosure provides a method for efficiently and industrially producing graphene from a high-purity solid carbon source.

[0033] Graphene and graphene defects

[0034] Graphene is composed of a single layer of sp 2 A material with a two-dimensional honeycomb structure formed by hybrid orbital carbon atoms. A single layer of ideal graphene has a thickness of about 0.335 nm, which corresponds to the thickness of one carbon atom. Graphene with a two-dimensional crystal structure has many advantageous features, such as a high specific surface area and favorable electrical, thermal and mechanical properties. For example, graphene forms a hexagonal lattice and resists various in-plane deformations due to its sp 2 Excellent mechanical properties due to the stability of the bond.

[0035] Potential applications of graphene include use in composite materials (e.g., as a reinforcing agent or thermal agent), field effect transistors, electromechanical systems, strain sensors, electronic devices, batteries, supercapacitors, micro-nano devices, hydrogen storage, and solar cells. The applications of graphene are expanding with the increasing availability of low-cost, high-quality graphene.

[0036] However, previous methods for producing graphene are prone to defects. In most cases, these defects can affect the mechanical properties of graphene and graphene-based composites as well as the thermal and electrical conductivity. Graphene defects can be divided into two different groups: intrinsic defects and extrinsic defects.

[0037] Intrinsic defects can be caused by non-sp 2Orbital hybridized carbon atoms. Intrinsic defects in graphene can cause multiple layers of graphene to stick together. Ideal graphene without defects will have no chemically bonded carbon atoms between layers. However, if there are intrinsic defects in graphene (e.g., holes, dangling bonds, or carbon atoms in a migrating state), the defective graphene layer can form new chemical bonds with adjacent carbon atoms in other graphene layers.

[0038] Extrinsic defects are defined by the crystalline order of graphene disturbed by foreign atoms or non-carbon atoms. Foreign atoms can be substitutional (replacing the original lattice atoms) or interstitial. In previous methods, foreign atoms are usually oxygen atoms or oxygen-containing functional groups, such as hydroxyl or carboxyl groups. In fact, it is difficult to completely remove oxygen atoms in graphene during the subsequent reduction process, and therefore the best way to produce graphene with low levels of oxygen-related defects is to prevent contamination during the synthesis of graphene itself, as taught in this article.

[0039] Defects can affect the mechanical, electrical, and thermal properties of graphene. For example, while ideal graphene has a thermal conductivity of about 5000 W / m·K, defects can change that thermal conductivity. It has been previously discovered that point defects or single vacancy defects in graphene can reduce thermal conductivity to 20% of the previous figure. When the defect concentration increases further, the thermal conductivity can be further reduced.

[0040] Various techniques can be used to evaluate graphene, including Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), inductively coupled plasma optical emission spectroscopy (ICP-OES), ICP-mass spectrometry (ICP-MS), proton induced x-ray emission, x-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), scanning tunneling microscopy (STM), atomic force microscopy (AFM), energy dispersive x-ray analysis (EDX), oxidative combustion, and / or thermogravimetric analysis.

[0041] In some embodiments, Raman spectroscopy is used to characterize graphene. Raman spectroscopy can be used to evaluate the electronic structure and identify the two-dimensional properties of graphene. Specifically, the D peak in the Raman spectrum of graphene does not exist in ideal graphene, but the intensity increases with the number of defects. The D peak is a signal that disrupts the symmetry of the graphene honeycomb lattice (such as grain boundaries, vacancies, edges, sp 3Hybridized carbon atoms, etc.) are sensitive. At the same time, the G peak is sensitive to the number of layers present in graphene. In some embodiments, the ratio I(D) / I(G) between the intensity of the D peak and the intensity of the G peak is used to estimate the defect level of graphene. However, when the disorder of graphene increases, I(D) / I(G) shows two different behaviors. There is a "low" defect density interval, in which I(D) / I(G) will increase as defects become higher. This phenomenon occurs until the "high" defect density interval, at which the increased defect density leads to a more amorphous carbon structure, point I(D) / I(G) will begin to decrease, thereby attenuating all Raman peaks. In addition, single-layer graphene can also be identified by analyzing the peak intensity ratio of the 2D band and the G band. For example, the I(2D) / I(G) ratio of defect-free single-layer graphene is equal to 2.

[0042] The oxygen content of graphene can be characterized by photoelectron spectroscopy. Ultraviolet-visible light spectroscopy is also used for chemical analysis of graphene dispersions in different solvents, because it can monitor the reaction process by using Beer's law and the linear relationship between the absorbance and concentration of the solution. In addition, XRD can be applied to evaluate the exfoliation and embedding of graphite and the final formation of graphene. The characteristic Bragg peak of graphite becomes wider as the number of layers decreases in the case of 2θ≈26°, and the characteristic Bragg peak eventually disappears for single-layer graphene. The number of layers can also be estimated relatively based on the x-ray diffraction pattern using the Scherrer formula. XPS can be applied to characterize the surface chemical structure of graphene by generating the bonding energy between carbon-carbon bonds and carbon-oxygen bonds in the material. The surface area of ​​graphene can be measured by the Brunauer-Emmett-Teller (BET) method.

[0043] Various forms of microscopy can be used to evaluate graphene and the degree of defects or the absence of defects. TEM can be used to characterize the atomic structure of graphene, such as quantifying the intrinsic defects of graphene (including vacancy defects, bond rotations, dislocation edges, grain boundaries) and visualizing the layer stacking. SEM can be used to observe the surface morphology of graphene. STM can provide information about the morphology and electronic properties of graphene in three dimensions. AFM can be used to characterize the number of layers of graphene.

[0044] Producing high-purity solid carbon sources

[0045] The present invention produces graphene from a high-purity solid carbon source.

[0046] In some embodiments, the solid carbon source is produced from oxidized carbon, including carbon monoxide (CO) and carbon dioxide (CO2). The oxidized carbon can be reduced to form solid carbon, and in some embodiments, a reducing gas (such as hydrogen) is used to perform the reduction. U.S. Pat. No. 8,679,444, incorporated herein by reference, describes various methods for producing solid carbon by reducing oxidized carbon.

[0047] There is a spectrum of reactions including carbon, hydrogen and oxygen that can produce solid carbon. Hydrocarbon pyrolysis is a range of equilibrium between hydrogen and carbon that favors solid carbon production, with little or no oxygen typically present. The Bosch reaction, also known as the carbon monoxide disproportionation reaction, is a range of equilibrium between carbon and oxygen that favors solid carbon production, with little or no hydrogen typically present. The Bosch reaction is a region of equilibrium where all of carbon, oxygen and hydrogen are present that favors solid carbon production. Other equilibria favor the production of carbon oxides or hydrocarbons (e.g., Sabatier and Fischer-Tropsch processes) without solid carbon products.

[0048] Bosch reaction Carbon dioxide is reduced using hydrogen to produce solid carbon and water. The temperature for the Bosch reaction can range from 400° C. to greater than 2000° C. In some embodiments, the reaction rate can be enhanced and the reaction temperature can be reduced by using a catalyst. In some embodiments, a solid carbon source is formed by the Bosch reaction. In some embodiments, the solid carbon formed by the Bosch reaction is used to produce graphene.

[0049] Wave reaction Also known as the carbon monoxide disproportionation reaction, it reduces carbon monoxide to produce solid carbon and carbon dioxide. In some embodiments, the solid carbon source is formed by a Bodo reaction. In some embodiments, the solid carbon formed by the Bodo reaction is used to produce graphene.

[0050] The type, purity, and homogeneity of the solid carbon source can be controlled by the reaction conditions (time, temperature, pressure, partial pressures of reactants), and in some embodiments, by the catalyst (including the size, formation method, and form of the catalyst).

[0051] In some embodiments, the temperature for producing the solid carbon source may be in the range of 400°C to 2000°C, for example, 400°C to 700°C, 400°C to 800°C, 400°C to 900°C, 400°C to 1000°C, 400°C to 1200°C, 400°C to 1400°C, 400°C to 900°C, 500°C to 600°C, 500°C to 700°C, 500°C to 800°C, 550°C to 650°C, 550°C to 750°C, 575°C to 625°C, 600°C to 800°C. 0°C to 650°C, 600°C to 700°C, 600°C to 800°C, 625°C to 675°C, 650°C to 700°C, 700°C to 1200°C, 700°C to 1400°C, 800°C to 1200°C, 800°C to 1400°C, 900°C to 1400°C, 1000°C to 1400°C, 1100°C to 1400°C, 1200°C to 1400°C, 1300°C to 1400°C, 1000°C to 2000°C or 1400°C to 2000°C.

[0052] In some embodiments, the solid carbon source is produced under pressure. In some embodiments, the pressure for producing the solid carbon may be in the range of 1 bar to 10 bar: for example, 1 bar to 2 bar, 1 bar to 3 bar, 1 bar to 4 bar, 1 bar to 5 bar, 1 bar to 6 bar, 1 bar to 7 bar, 1 bar to 8 bar, 1 bar to 9 bar, 2 bar to 3 bar, 2 bar to 4 bar, 2 bar to 5 bar, 2 bar to 6 bar, 2 bar to 7 bar, 2 bar to 8 bar, 2 bar to 9 bar, 2 bar to 10 bar, 3 bar to 4 bar, 3 bar to 5 bar, 3 bar to 6 bar, 3 bar to 7 bar, 3 bar to 8 bar, 2 bar to 9 bar, 2 bar to 10 bar, 3 bar to 4 bar, 3 bar to 5 bar, 3 bar to 6 bar, 3 bar to 7 bar, 3 bar to 8 bar, 3 ...3 bar, 2 bar to 4 bar, 2 bar to 5 bar, 2 bar to 6 bar, 2 bar to 7 bar, 3 bar to 8 bar, 3 bar to 9 bar, 2 bar to 10 bar, 3 bar to 4 bar, 3 bar to 5 bar, 3 bar to 6 bar, 3 bar to 7 bar, 3 bar to 8 bar, 3 bar to 9 bar, 2 bar to 3 bar, 2 bar to 3 bar, 2 bar to 4 bar, 2 bar to 5 bar, 2 bar to 6 bar, 2 bar to 7 bar, 3 bar to 8 bar, 2 bar to 9 bar, In some embodiments, the solid carbon source is produced under atmospheric pressure. In some embodiments, the solid carbon source is produced under vacuum.

[0053] The use of an inert gas during the production of a solid carbon source is beneficial in limiting the introduction of foreign atoms, such as introducing foreign atoms present in the atmosphere into the system. In some embodiments, the solid carbon source is produced under an inert gas. In some embodiments, the inert gas is a rare gas. In some embodiments, the inert gas is argon or helium.

[0054] In some embodiments, the reaction includes a catalyst. The reaction kinetics that are conducive to forming the desired type of solid carbon can be established by including a suitable catalyst. For example, the reaction can be accelerated and the reaction can be operated at a lower temperature in the presence of a catalyst. In some embodiments, such as when a catalyst is used, the reaction can proceed to complete within 5 seconds (for example, within 4 seconds, 3 seconds, 2 seconds, 1 second or 0.5 seconds). In some embodiments, the catalyst is iron. In some embodiments, the catalyst includes a coating, a sheet, a lattice structure, a honeycomb structure, etc. In some embodiments, the catalyst includes a repeated honeycomb. The catalyst of a lattice or honeycomb structure is advantageous in that a unique structure can increase the surface area of ​​the catalyst while also maintaining the strength of the catalyst.

[0055] The solid carbon source may be in the form of graphite, graphene, carbon black, amorphous carbon, fibrous carbon, buckminsterfullerene (e.g., buckyballs, single-walled carbon nanotubes, and multi-walled carbon nanotubes), etc. In some embodiments, the solid carbon source comprises greater than 90% (w / w) amorphous carbon, such as greater than 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5%, 99.9%, 99.95, or 99.99% (w / w) amorphous carbon. In some embodiments, the solid carbon source comprises greater than 90% (w / w) graphitic carbon, such as greater than 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5%, 99.9%, 99.95, or 99.99% (w / w) graphitic carbon.

[0056] The resulting solid carbon source is of high purity. The present method is advantageous in that, because the solid carbon source is of high purity, the graphene produced includes substantially few defects. In some embodiments, the solid carbon source is greater than 99.99% (w / w) elemental carbon (e.g., greater than 99.995% (w / w), greater than 99.999% (w / w), greater than 99.9995% (w / w), or greater than 99.9999% (w / w) elemental carbon).

[0057] Producing high-quality graphene

[0058] The present invention relates to the synthesis of graphene by flash Joule heating (FJH) of a high-purity solid carbon source and is advantageous in that the resulting graphene includes very few defects compared to previous methods. In FJH, a voltage pulse is applied to a solid carbon source, thereby rapidly heating the solid carbon source to produce graphene. FJH is described in U.S. Patent Publication No. US20210206642A1, which is incorporated herein by reference.

[0059] The present method produces graphene rapidly from a high-purity solid carbon source. In some embodiments, the duration of the voltage pulse may be within 5 seconds (e.g., within 4 seconds, 3 seconds, 2 seconds, 1 second, 500 milliseconds, 400 milliseconds, 300 milliseconds, 200 milliseconds, 100 milliseconds, 10 milliseconds, 1 millisecond, 500 microseconds, 100 microseconds, 10 microseconds). The voltage on the sample may be between 1V / cm and 4000V / cm. Applying a voltage pulse to form graphene on the material may include applying a lot of voltage pulses on the material. In some embodiments, the number of voltage pulses may be within the range of 1 pulse and 100 pulses.

[0060] The present method of producing Graphene is advantageous in that it can produce a large amount of high-quality or high-purity graphene that industry and academia all need, and promotes Graphene to enter further commercial application. The block graphene of known current production is extremely prone to defects, and has a negative impact on the mechanical properties, thermal properties and electrical properties of Graphene. In some embodiments, the present method produces at least one gram of graphene (for example, at least 2 grams, 3 grams, 4 grams, 5 grams, 6 grams, 7 grams, 8 grams, 9 grams, 10 grams, 20 grams, 25 grams, 30 grams, 40 grams, 50 grams, 75 grams, 100 grams, 150 grams, 200 grams, 250 grams, 300 grams, 400 grams, 500 grams, 750 grams, 1 kilogram or more) per hour or every day on a large scale.

[0061] The present method for producing graphene is also advantageous in that it has produced high yields of graphene from a solid carbon source. In some embodiments, the yield of graphene produced from a solid carbon source is at least 90% (w / w) (e.g., at least 91%, at least 92%, at least 93%, at least 94%, at least 95%, at least 96%, at least 97%, at least 98%, at least 99%, at least 99.5%, at least 99.9%, at least 99.95%, at least 99.99%, at least 99.995%, at least 99.999%, at least 99.9995%, or at least 99.9999%).

[0062] In some embodiments, graphene has properties close to those of ideal graphene due to the absence of extrinsic defects and / or intrinsic defects.

[0063] In some embodiments, the graphene has at least 10 4 S / m (e.g., at least 1.5x10 4 S / m, at least 2x10 4 S / m, at least 2.5x10 4 S / m, at least 3x10 4 S / m, at least 3.5x10 4 S / m, at least 4x10 4S / m, at least 4.5x10 4 S / m, at least 5x10 4 S / m, at least 5.5x10 4 S / m, at least 6x10 4 S / m, at least 6.5x10 4 S / m, at least 7x10 4 S / m, at least 7.5x10 4 S / m, at least 8x10 4 S / m, at least 8.5x10 4 S / m, at least 1.5x10 4 S / m, at least 9x10 4 S / m or at least 9.5x10 4 In some embodiments, the conductivity of graphene is measured by conductive atomic force microscopy (C-AFM).

[0064] In some embodiments, the graphene has a thickness greater than 1000 m 2 / g (for example, greater than 1100m 2 / g, greater than 1200m 2 / g, greater than 1300m 2 / g, greater than 1400m 2 / g, greater than 1500m 2 / g, greater than 1600m 2 / g, greater than 1700m 2 / g, greater than 1800m 2 / g, greater than 1900m 2 / g, greater than 2000m 2 / g, greater than 2100m 2 / g, greater than 2200m 2 / g, greater than 2300m 2 / g, greater than 2400m 2 / g or greater than 2500m 2 In some embodiments, the SSA of graphene is measured by the Brunauer-Emmett-Teller (BET) model.

[0065] In some embodiments, the graphene is a graphene flake, and the graphene flake has an average lateral size (D50) of at least 10 μm (e.g., at least 50 μm, at least 100 μm, at least 150 μm, at least 200 μm, at least 250 μm, at least 300 μm, at least 350 μm, at least 400 μm, at least 450 μm, at least 500 μm, at least 550 μm, at least 600 μm, at least 650 μm, at least 700 μm, at least 750 μm, at least 800 μm, at least 850 μm, at least 900 μm, at least 950 μm, or at least 1 mm). In some embodiments, the average lateral size of the graphene flakes is measured by static light scattering.

[0066] In some embodiments, the graphene contains less than 200 ppm of extrinsic defects (e.g., less than 100, 75, 50, 25, 10, 5, or 1 ppm of extrinsic defects). A common extrinsic defect when producing graphene is the contaminant oxygen. In some embodiments, the graphene contains less than 200 ppm of oxygen (e.g., less than 100, 75, 50, 25, 10, 5, or 1 ppm of oxygen). The level of extrinsic defects can be determined by Raman spectroscopy.

[0067] The present method minimizes intrinsic defects as well as extrinsic defects. In some embodiments, the graphene contains less than 0.01% intrinsic defects (e.g., less than 0.005%, 0.001%, 0.0005%, or 0.0001% intrinsic defects). Intrinsic defects include sp 3 , and the standard sp 2 In some embodiments, graphene includes greater than 90% sp 2 Hybridized carbon atoms (e.g., greater than 95%, 96%, 97%, 98%, 99%, 99.9%, 99.95%, 99.99%, 99.995%, 99.999%, 99.9995%, or 99.9999% sp 2 In some embodiments, the graphene contains less than 10% sp 3 Hybridized carbon atoms (e.g., less than 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05%, 0.01%, 0.005%, 0.001%, 0.0005%, or 0.0001% sp 3 Hybridized carbon atoms). Carbon hybridization can be determined via X-ray photoelectron spectroscopy (XPS) or Raman spectroscopy.

[0068] In some embodiments, graphene includes a plurality of graphene sheets. Raman spectroscopy or ellipsometry can be used to evaluate the number of layers. Due to the absence of extrinsic defects, the graphene sheets do not adhere to and maintain their 2D properties when stacked, such as a low I(D) / (G) ratio determined by Raman spectroscopy. In some embodiments, graphene has an I(D) / I(G) ratio of less than 0.2 (e.g., less than 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0.11, 0.10, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, 0.01, 0.005, 0.001, 0.0005, 0.0001, 0.00005, or 0.00001). In some embodiments, the graphene has an I(2D) / I(G) ratio in a range between 0.5 and 2 (e.g., between 0.6 and 2, between 0.7 and 2, between 0.8 and 2, between 0.9 and 2, between 1 and 2, between 1.1 and 2, between 1.2 and 2, between 1.3 and 2, between 1.4 and 2, between 1.5 and 2, between 1.6 and 2, between 1.7 and 2, between 1.8 and 2, or between 1.9 and 2).

[0069] In one embodiment, the present invention provides a method for producing graphene, wherein a solid carbon source is produced in a first chamber, the solid carbon source is transferred to a second chamber, wherein the second chamber includes a plurality of electrodes, and a voltage pulse is applied to the solid carbon source to convert the solid carbon source into graphene. However, in some embodiments, the solid carbon source and graphene can be produced in the same chamber. In one embodiment, the present invention provides a method for producing graphene, wherein a solid carbon source is produced in a chamber, wherein the chamber includes a plurality of electrodes, and the plurality of electrodes apply a voltage pulse to the solid carbon source to convert the solid carbon source into graphene. The advantage of a closed system (such as two interconnected chambers or a single chamber) may be that it minimizes the risk of exposing the system to foreign substances (such as the atmosphere).

[0070] Figure 1A , Figure 1B and Figure 1C One embodiment of a chamber is depicted. In some embodiments, the chamber is non-conductive and / or non-reactive. In some embodiments, the chamber withstands high heat and pressure, such as temperatures in excess of 700°C and pressures in excess of 200 PSI. In some embodiments, the chamber comprises Monel K500. Figure 2A and Figure 2B Describe for Figure 1A , Figure 1B and Figure 1C The catalyst may be iron.

[0071] The electrodes may be stainless and withstand high temperatures. In some embodiments, the electrodes include Inconel. Inconel is advantageous in that it is highly conductive.

[0072] In some embodiments, the graphene production system includes polytetrafluoroethylene (PTFE). In some embodiments, the graphene production system includes a chamber lined with PTFE. In some embodiments, the graphene production system includes a carbon steel pipe lined with PTFE, such as a carbon steel schedule 40 pipe lined with PTFE. PTFE is advantageous in that it is a stainless material that can withstand high temperatures and pressures.

[0073] The chamber may include a seal. In some embodiments, the seal comprises silicon, such as a mica silicon composite material. Mica silicon composite materials are advantageous in that they provide high heat resistance and tight sealing under high pressure. Figure 3 Describe for Figure 1A , Figure 1B and Figure 1C An embodiment of a seal for a chamber.

[0074] Once graphene is put into production, it is prepared by various methods for the manufacture of byproducts. The preparation method includes, for example, solution compounding, melt blending, in-situ polymerization and layer-by-layer assembly. The advantage of the graphene disclosed herein is that it does not need to be post-processed (e.g., purified) before being prepared for secondary use. By producing graphene from a high-purity solid carbon source, the post-processing steps usually required when manufacturing graphene can be avoided. In some embodiments, graphene can be mixed with a binder (e.g., a polymer solution) or a dispersion to form a mixture without performing a previous purification step. In some embodiments, the binder is a polymer solution. The graphene present in the mixture may be between 0.1% (w / w) and 99.99% (w / w) (e.g., between 0.1% (w / w) and 1% (w / w), between 1% (w / w) and 5% (w / w), between 5% (w / w) and 10% (w / w), 10% and 25% (w / w), 25% (w / w) and 50% (w / w), 50% (w / w) and 75% (w / w), or between 90% (w / w) and 99.99% (w / w)). In some embodiments, the graphene present in the mixture may be greater than 90% (w / w) (e.g., greater than 91% (w / w), 92% (w / w), 93% (w / w), 94% (w / w), 95% (w / w), 96% (w / w), 97% (w / w), 98% (w / w), or 99% (w / w)).

[0075] Example

[0076] The following examples are put forth so as to provide those skilled in the art with a complete disclosure and description of how to perform, make and test the methods and compounds claimed herein and are intended to be merely illustrative of the invention and are not intended to limit the scope of what the inventors regard as their invention.

[0077] Example 1: Producing high-quality graphene

[0078] A stoichiometric mixture of carbon dioxide and hydrogen is added to a first chamber according to the Bosch reaction. The chamber is heated to 600°C and pressurized with argon. After one hour, the chamber is purged with argon and the resulting solid carbon is transferred to a second chamber. The solid carbon is deposited between two electrodes connected to a plurality of capacitors operable to apply a voltage pulse. The voltage pulse has a duration of 10 milliseconds and applies a voltage between 100V and 400V to the solid carbon producing high purity graphene.

Claims

1. A method for producing graphene, the method comprising: a. providing a high purity solid carbon source, wherein the solid carbon source is greater than 99.99% (w / w) elemental carbon; as well as b. applying a voltage pulse to the solid carbon source to convert the solid carbon source into graphene, wherein the graphene comprises less than 200 ppm of extrinsic defects.

2. The method of claim 1, wherein the solid carbon source is greater than 99.995% (w / w) elemental carbon.

3. The method of claim 1, wherein the solid carbon source is greater than 99.999% (w / w) elemental carbon.

4. The method of claim 1, wherein the solid carbon source is greater than 99.9995% (w / w) elemental carbon.

5. The method of claim 1, wherein the solid carbon source is greater than 99.9999% (w / w) elemental carbon.

6. The method of any one of claims 1 to 5, wherein the graphene comprises less than 100 ppm of extrinsic defects.

7. The method of any one of claims 1 to 5, wherein the graphene comprises less than 50 ppm of extrinsic defects.

8. The method of any one of claims 1 to 5, wherein the graphene comprises less than 25 ppm of extrinsic defects.

9. The method of any one of claims 1 to 5, wherein the graphene comprises less than 10 ppm of extrinsic defects.

10. The method of any one of claims 1 to 5, wherein the graphene comprises less than 5 ppm of extrinsic defects.

11. The method of any one of claims 1 to 10, wherein the graphene comprises less than 1 ppm of extrinsic defects.

12. The method of any one of claims 1 to 11, wherein the extrinsic defects are evaluated by Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), inductively coupled plasma optical emission spectroscopy (ICP-OES), ICP-mass spectrometry (ICP-MS), proton induced x-ray emission, x-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), scanning tunneling microscopy (STM), atomic force microscopy (AFM), energy dispersive x-ray analysis (EDX), oxidative combustion and / or thermogravimetric analysis.

13. The method of any one of claims 1 to 12, wherein the extrinsic defect is oxygen.

14. The method of claim 13, wherein the graphene contains less than 200 ppm of oxygen.

15. The method of any one of claims 1 to 14, wherein the graphene contains less than 0.01% intrinsic defects.

16. The method of any one of claims 1 to 15, wherein the intrinsic defects include non-sp 2 Orbital hybridization of carbon atoms.

17. The method of any one of claims 1 to 16, wherein the graphene contains less than 0.01% sp 3 .

18. The method according to any one of claims 1 to 17, wherein the sp 2 The percentage is at least 95%.

19. The method of any one of claims 1 to 18, wherein the graphene has an I(D) / I(G) ratio of less than 0.2 as measured by Raman spectroscopy.

20. The method of any one of claims 1 to 19, wherein the graphene has an I(2D) / I(G) ratio between 0.5 and 2 as measured by Raman spectroscopy.

21. The method of any one of claims 1 to 20, wherein the conductivity of the graphene is at least 10 4 S / m.

22. The method of any one of claims 1 to 21, wherein the specific surface area (SSA) of the graphene is greater than 1000 m 2 / g.

23. The method of any one of claims 1 to 22, wherein the graphene is graphene flakes, and wherein the graphene flakes have an average lateral size (D50) of at least 10 μm.

24. The method according to any one of claims 1 to 23, wherein the subsequent step b) does not purify the graphene.

25. The method of any one of claims 1 to 24, wherein the subsequent step b) does not remove extrinsic defects.

26. The method of any one of claims 1 to 25, wherein the solid carbon source comprises greater than 90% (w / w) amorphous carbon.

27. The method of any one of claims 1 to 25, wherein the solid carbon source comprises greater than 90% (w / w) graphitic carbon.

28. The method of any one of claims 1 to 27, wherein the solid carbon source is produced by reducing carbon dioxide or carbon monoxide using hydrogen.

29. The method of any one of claims 1 to 27, wherein the solid carbon source is produced from carbon dioxide and hydrogen via a Bosch reaction.

30. The method of any one of claims 1 to 28, wherein the amount of hydrogen provided is greater than the stoichiometric ratio required to reduce the carbon dioxide or the carbon monoxide.

31. The method of any one of claims 1 to 27, wherein the solid carbon source is produced from carbon monoxide via a Bodo reaction.

32. The method of any one of claims 29 to 31, wherein the reaction comprises a catalyst or a catalyst precursor.

33. The method of any one of claims 29 to 32, wherein the reaction occurs at room temperature.

34. A method as claimed in any one of claims 29 to 33, wherein the reaction occurs at a temperature between 450°C and 2000°C.

35. The process of any one of claims 1 to 34, wherein step b) is performed at atmospheric pressure.

36. The method of any one of claims 1 to 35, wherein the method produces at least one gram of graphene.

37. The method of any one of claims 1 to 36, wherein the yield of graphene produced from the solid carbon source is at least 90%.

38. The method of any one of claims 1 to 37, wherein the method further comprises step c) mixing the graphene with a binder or dispersant without further purification.

Citation Information

Patent Citations

  • Flash joule heating synthesis method and compositions thereof

    US20210206642A1

  • Method for producing solid carbon by reducing carbon oxides

    US8679444B2